2020
DOI: 10.3389/fchem.2020.583176
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Annulation of Gossypol by Laccase to Produce Safe Cottonseed Protein

Abstract: The presence of the phenol gossypol has severely limited the utilization of cottonseed meal and oil in the food and animal feed industries. Highly efficient means of biodegradation of gossypol and an understanding of the cytotoxicity of its degradation products remain outside current knowledge and are of universal interest. In this work, we showed for the first time that laccase can catalyze the intramolecular annulation of the aldehyde and hydroxyl groups of gossypol for the o-semiquinone radical and originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The polyphenolic structure of FG makes this compound a potential substrate for laccases. Wang et al recently reported that commercial laccase from Trametes versicolor could catalyze the intramolecular annulation of the hydroxyl and aldehyde groups of FG [23]. In this work, we studied the FG-degrading capacity of bacterial laccases for the first time.…”
Section: Introductionmentioning
confidence: 95%
“…The polyphenolic structure of FG makes this compound a potential substrate for laccases. Wang et al recently reported that commercial laccase from Trametes versicolor could catalyze the intramolecular annulation of the hydroxyl and aldehyde groups of FG [23]. In this work, we studied the FG-degrading capacity of bacterial laccases for the first time.…”
Section: Introductionmentioning
confidence: 95%
“…According to the United Nations Food and Agriculture Organization and the World Health Organization, the acceptable levels of gossypol in cottonseed products are 450–600 ppm (free gossypol) and 12,000 ppm (total gossypol) [ 102 ]. Many well-researched strategies, including genetic engineering [ 103 ], enzyme detoxification [ 104 , 105 ], fermentation, and solvent extractions have been applied to eradicate the gossypol-containing glands from cottonseed.…”
Section: Seeds From Fibre Crops That Are Potential Sources Of Polyphe...mentioning
confidence: 99%
“…One way to reduce the toxicity of gossypol and enhance its biological properties is to convert it into azepine derivatives, such as Schiff bases or hydrazones. The Schiff base or hydrazone gossypol can undergo Schiff base formation [58,59], ozonation [15], oxidation [60], and methylation [61] to form gossypol derivatives.…”
Section: Mass Spectrometry Analysis Of Intermediate Productsmentioning
confidence: 99%
“…Previous studies have focused on the oxidation of gossypol by H. armigera P450 enzymes [57]. Laccase cyclization-hydroxyl aldehyde condensation [61] is a reaction of gossypol that renders it less toxic. This finding also coincides with the fact that enzymes have a wide range of substrates.…”
Section: Mass Spectrometry Analysis Of Intermediate Productsmentioning
confidence: 99%